PENGARUH PEMBERIAN INFORMASIMELALUI MEDIA KONVESIONAL TERHADAP PENGETAHUAN DAN SIKAP IBU NIFAS DALAM PEMBERIAN ASI EKSKLUSIF DI RSU SEMBIRING TAHUN 2025 - Yanti, Mutiara Dwi; Siagian, Nurul Aini; Sitanggang, Sari (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2025)
Breast milk (ASI) serves as the main source of nutrition for infants during their first six months, offering a complete range of nutrients, antibodies, essential fatty acids, and hormones. Additionally, breastfeeding helps strengthen the emotional connection between mother and child (Sakinah et al., 2024). In Indonesia, the rate of exclusive breastfeeding for six months remains low at only 32.3%, with North Sumatra recording a slightly higher rate of 40.66% in 2019. Contributing factors to this low prevalence include aggressive marketing of formula milk and breast milk substitutes, as well as limited maternal knowledge about the importance of exclusive breastfeeding (Rianah Hernah et al., 2024). This research aimed to assess the impact of information delivered through conventional media on postpartum mothers' knowledge and attitudes toward exclusive breastfeeding at Sembiring General Hospital in 2025. The study was conducted from January to June 2025 using a quasi-experimental method with a one-group pretest-posttest design. The population included all breastfeeding postpartum mothers at RSU Sembiring, with a total of 16 participants selected through purposive sampling. Based on bivariate analysis using the T-test, the results showed a p-value of 0.000 (p < 0.05), indicating that the alternative hypothesis (Ha) is accepted. This signifies a significant difference in attitudes before and after the intervention. Thus, it can be concluded that providing information through conventional media had a positive effect on the attitudes of postpartum mothers at RSU Sembiring, Deli Tua, in 2025.